Green coke and judgment method thereof, graphite and preparation method thereof, negative electrode and battery

By solvent extraction and heat treatment of the raw coke, high-quality raw coke with an F value of ≥0.10%, and graphite is prepared using the raw coke, which solves the problem of poor electrochemical performance of the existing graphite and achieves high-speed fast charging performance promote.

CN119503757APending Publication Date: 2025-02-25HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311057180.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The quality of the graphite, the negative electrode material of the existing lithium-ion battery, is affected by the coking properties, resulting in poor electrochemical performance, especially under high-speed fast charging conditions.

Method used

By solvent extraction and heat treatment of the raw coke, high-quality raw coke with an F value of ≥0.10%, graphite is prepared by using the raw coke, and the electrochemical properties of the graphite are improved through steps such as graphitization and carbon coating.

Benefits of technology

It improves the electrochemical performance of graphite, enhances its lithium storage channel and lithium embedded speed under high-rate fast charging conditions, and improves fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004406377510000061
    Figure BDA0004406377510000061
Patent Text Reader

Abstract

The invention relates to the technical field of negative electrode material preparation, and discloses green coke and a judgment method thereof, graphite and a preparation method thereof, a negative electrode and a battery. F of the green coke is greater than or equal to 0.10%, F = M1 / Mc * 100%, in the formula, Mc is the mass of the green coke, M1 is the mass of a residue obtained by performing heat treatment on an obtained substance dissolved in a solvent after the green coke is extracted by the solvent, the solvent is a solvent with a solvent polarity parameter of 4.0-4.5, and the heat treatment conditions are 500-600 DEG C and air atmosphere. The preparation method of the graphite comprises the step of carrying out graphitization treatment on the green coke. The negative electrode is prepared from the graphite. The battery comprises the negative electrode. The judgment method of the high-quality green coke comprises the following steps: calculating according to a formula F = M1 / Mc * 100% to obtain an F value, and if F is greater than or equal to 0.10%, determining that the green coke is the high-quality green coke for preparing graphite. The green coke provided by the invention can be used for preparing graphite with good performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode material preparation, and in particular to high-quality raw coke and a method for determining the same, graphite and a method for preparing the same, a negative electrode and a battery. Background Art

[0002] Lithium-ion batteries are widely used in new energy and other fields due to their high energy density and excellent cycle performance. Graphite, as the negative electrode material of lithium-ion batteries, currently has a very mature application market. From the perspective of raw materials, the properties of coke will greatly affect the quality of graphitized products.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The purpose of the present invention is to provide high-quality raw coke and a method for determining the same, graphite and a method for preparing the same, a negative electrode and a battery.

[0005] The present invention is achieved in that:

[0006] In a first aspect, the present invention provides a green coke, characterized in that the particle size of the green coke is 1 to 100 μm, F ≥ 0.10%; wherein F = M1 / M c ×100%, where M c is the mass of green coke, M1 is the mass of the residue obtained by heat treatment of the substance dissolved in the solvent after solvent extraction of the green coke, the solvent has a solvent polarity parameter of 4.0-4.5, and the heat treatment conditions are 500-600°C and air atmosphere.

[0007] In an optional embodiment, the solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran;

[0008] In an optional embodiment, the particle size of the green coke is 6 to 15 μm.

[0009] In alternative embodiments, the green coke is petroleum coke, needle coke or pitch coke.

[0010] In an optional embodiment, the mass of the residue is determined by:

[0011] The green coke is extracted with a solvent, and the extract is heat-treated after sufficient extraction, or the concentrated solution is concentrated and then heat-treated to obtain a residue, and the mass of the residue is M1.

[0012] In an optional embodiment, the concentration to the coke quality M c 1 / 4 to 1 / 2 of the concentrate is obtained.

[0013] In an optional embodiment, the heat treatment time is 2 to 3 hours.

[0014] In a second aspect, the present invention provides graphite, which is prepared using the raw coke according to any one of the aforementioned embodiments.

[0015] In an optional embodiment, the graphitization degree of the graphite is greater than 90%; and the 3C / 0.5C capacity retention rate of the graphite is greater than 70%.

[0016] In a third aspect, the present invention provides a method for preparing graphite, comprising graphitizing the raw coke according to any one of the aforementioned embodiments.

[0017] In an optional embodiment, the process further includes shaping the green coke before graphitization.

[0018] In an optional embodiment, a graphitized product is obtained after graphitization, and the graphitization includes: coating asphalt or tar on the surface of the graphitized product particles, carbonizing at 1100-1300° C. for 7-8 hours, and the mass ratio of asphalt or tar to graphitized product is 0.01-0.05:1;

[0019] In an optional embodiment, the graphitization treatment temperature is 2800-3200°C.

[0020] In a fourth aspect, the present invention provides a negative electrode, which is made of the graphite according to the aforementioned embodiment.

[0021] In a fifth aspect, the present invention provides a fast-charging lithium-ion battery, comprising a negative electrode as described in the aforementioned embodiment.

[0022] In a sixth aspect, the present invention provides a method for determining the coke production of graphite, comprising:

[0023] The mass is M c The raw coke is extracted with a solvent, and the obtained substance dissolved in the solvent is heat-treated to obtain a mass M1 of the residue obtained by the heat treatment, wherein the solvent has a solvent polarity parameter of 4.0-4.5, and the heat treatment conditions are 500-600° C. and air atmosphere;

[0024] According to the formula F = M1 / M c ×100% to calculate the F value. If F≥0.10%, it is high-quality green coke for making graphite.

[0025] In an optional embodiment, the solvent is selected from at least one of chloroform, ethyl acetate, and tetrahydrofuran.

[0026] In an optional embodiment, the particle size of the green coke is 1 to 100 μm; preferably, the particle size of the green coke is 6 to 15 μm.

[0027] In an optional embodiment, the method for obtaining the mass M1 of the residue is:

[0028] The green coke is extracted with a solvent, and the extract is heat-treated after sufficient extraction, or the concentrated solution is concentrated and then heat-treated to obtain a residue, and the mass of the residue is M1.

[0029] In an optional embodiment, the concentration to the quality M of the raw coke c 1 / 4 to 1 / 2 of the concentrate is obtained.

[0030] In an optional embodiment, the heat treatment time is 2 to 3 hours.

[0031] The present invention has the following beneficial effects:

[0032] After the raw coke is extracted from substances that can be dissolved in substances with polarity parameters of 4.0 to 4.5, it is heat-treated in the air to produce a series of chemical changes to obtain a residue. The mass of the residue is compared with the mass of the raw coke to obtain the F value. The inventors found that if F ≥ 0.10%, the raw coke has a self-bonding effect during the graphitization process to obtain a secondary granular material, which increases the internal isotropy, reduces the degree of graphite orientation, increases the lithium storage channels of the graphitized product, and improves the lithium insertion speed, thereby increasing the fast charging performance.

[0033] Therefore, the raw coke provided by the present invention can be used to prepare graphite with good electrochemical properties; the graphite provided by the present invention, because it is prepared using the raw coke provided by the present invention, has good electrochemical properties and is suitable for preparing the negative electrode of high-rate fast-charging lithium batteries. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0035] The following is a detailed description of the high-quality green coke and its determination method, graphite and its preparation method, negative electrode, and battery provided in the embodiments of the present invention.

[0036] The green coke provided in the embodiment of the present invention has a particle size of 1 to 100 μm, F ≥ 0.10%; wherein F = M1 / M c ×100%, where M c is the mass of green coke, M1 is the mass of the residue obtained by heat treatment of the substance dissolved in the solvent after solvent extraction of the green coke, the solvent has a solvent polarity parameter of 4.0-4.5, and the heat treatment conditions are 500-600°C and air atmosphere.

[0037] After extracting the substance soluble in the polarity parameter of 4.0 to 4.5 from the raw coke, a residue is obtained after heat treatment in air to undergo a series of chemical changes. The mass of the residue is compared with the mass of the raw coke to obtain the F value. The inventors found that if F ≥ 0.10%, it indicates that the raw coke can be used to prepare graphite so that the prepared graphite has good electrochemical properties, especially for preparing the negative electrode of high-rate fast-charging lithium batteries. Therefore, the raw coke provided by the present invention can produce graphite with good electrochemical properties.

[0038] Furthermore, in order to verify whether the selected F value of the raw coke meets the requirements, the method used is:

[0039] Weigh the mass of raw coke M c , extracting green coke with a solvent having a polarity parameter of 4.0 to 4.5 to obtain an extract; directly subjecting the extract to heat treatment, or concentrating the extract to obtain a concentrated solution and then subjecting the concentrated solution to heat treatment; obtaining a residue after the heat treatment, and weighing the mass of the residue as M1;

[0040] The heat treatment is performed at a temperature of 500 to 600° C. (eg, 500° C., 550° C., or 600° C.) in an air atmosphere.

[0041] According to the formula F = M1 / M c ×100% to calculate the F value, and if F≥0.10%, it meets the use requirements.

[0042] Preferably, in a more efficient solution, the extract is generally concentrated and then heat treated, for example, the extract is concentrated to a coke quality M c 1 / 4 to 1 / 2 (e.g. 1 / 4, 1 / 3 or 1 / 2) of the concentrate is obtained, and the concentrate is then heat-treated. During the high-temperature heat treatment process, the solvent in the concentrate evaporates, and the solute therein undergoes a series of reactions to obtain a residue.

[0043] Furthermore, the solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran.

[0044] Furthermore, in order to subsequently produce graphite with good performance and to fully extract the soluble substances in the green coke, the particle size of the green coke is 1 to 100 μm, preferably 6 to 15 μm.

[0045] Optionally, the green coke is petroleum coke, needle coke or pitch coke.

[0046] The graphite provided in the embodiment of the present invention is obtained by graphitizing the raw coke provided in the embodiment of the present invention. Since the graphite is obtained by using the raw coke provided in the embodiment of the present invention, it has good electrochemical properties and is suitable for preparing the negative electrode of high-rate fast-charging lithium battery.

[0047] The method for preparing graphite provided by the embodiment of the present invention comprises: performing graphitization treatment using the green coke provided by the embodiment of the present invention.

[0048] The method for preparing graphite provided by the present invention adopts raw coke with F≥0.10% as raw material, so the prepared graphite has good electrochemical properties and is suitable for preparing negative electrodes of high-rate fast-charging lithium batteries.

[0049] Preferably, the 3C / 0.5C capacity retention rate of graphite is greater than 70%;

[0050] Preferably, the graphitization degree of the graphite is greater than 90%.

[0051] Specifically, the preparation method is:

[0052] S1. Select raw materials for preparation:

[0053] The green coke with F≥0.10% is selected, and the particle size is 1 to 100 μm, preferably 6 to 15 μm.

[0054] S2, Plastic Surgery:

[0055] By shaping, the shape of the raw coke particles is processed into a spherical or quasi-spherical shape.

[0056] S3. Graphitization treatment:

[0057] The raw coke is placed at a temperature of 2800-3200°C (e.g., 2800°C, 3000°C, or 3200°C) for graphitization for 1.5-2.5h (e.g., 1.5h, 2h, or 2.5h) to obtain a graphitized product, which is crushed and sieved to obtain a graphitized product with a particle size of 1-100μm, preferably 6-15μm.

[0058] S4, Carbon coating after graphitization:

[0059] The graphitized product is mixed with asphalt or tar so that the asphalt or tar is coated on the surface of the graphitized product particles, and carbonized at 1100-1200°C (for example, 1100°C, 1150°C or 1200°C) for 7-8h (for example, 7, 7.5h or 8h), and the mass ratio of asphalt or tar to graphitized product is 0.01-0.05:1 (for example, 0.01:1, 0.03:1 or 0.05:1).

[0060] It should be noted that, in the above steps, step S4 is not an essential step, and step S4 may or may not be performed depending on the properties of the graphite to be prepared.

[0061] An anode provided in an embodiment of the present invention is made of the graphite provided in an embodiment of the present invention, has good electrochemical properties, and is suitable for use as a cathode for a lithium battery with a high rate and fast charge.

[0062] A fast-charging lithium-ion battery provided in an embodiment of the present invention comprises the negative electrode provided in an embodiment of the present invention.

[0063] A method for determining high-quality raw coke for graphite production provided by an embodiment of the present invention comprises:

[0064] The mass is M c The raw coke is extracted with a solvent, and the obtained substance dissolved in the solvent is heat-treated to obtain a mass M1 of the residue obtained by the heat treatment, wherein the solvent has a solvent polarity parameter of 4.0 to 4.5, and the heat treatment conditions are 500 to 600° C. and an air atmosphere;

[0065] According to the formula F = M1 / M c ×100% to calculate the F value. If F≥0.10%, it is high-quality green coke for making graphite.

[0066] Preferably, the solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran. The above solvents are suitable for use in the present invention.

[0067] Preferably, the particle size of the green coke is 1 to 100 μm, preferably 6 to 15 μm.

[0068] Furthermore, the method for obtaining the mass M1 of the residue is:

[0069] The green coke is extracted with a solvent, and after sufficient extraction, the extract is concentrated to obtain a concentrated solution, and the concentrated solution is placed at 500 to 600° C. (e.g., 500° C., 550° C., or 600° C.) in an air atmosphere for heat treatment to obtain a residue, and the mass of the residue is M1;

[0070] Preferably, in a more efficient solution, heat treatment is performed after concentration, and specifically, for example, the coke can be concentrated to a mass M of green coke. c 1 / 4 to 1 / 2 (e.g. 1 / 4, 1 / 3 or 1 / 2) of the total weight of the product and then heat-treating the product;

[0071] Preferably, the heat treatment time is 2 to 3 h (eg, 2 h, 2.5 h or 3 h).

[0072] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0073] Table 1 Various cokes used in the present invention:

[0074]

[0075]

[0076] Example 1

[0077] Petroleum coke was selected as the raw material, and the parameters of the petroleum coke are shown in Table 1.

[0078] Verify whether the petroleum coke is high-quality green coke, specifically:

[0079] The petroleum coke was placed in an oven at 100°C and dried to obtain a powder with a particle size of 6 to 15 μm. c ) The above petroleum coke powder is mixed evenly with 100ml tetrahydrofuran (polarity is 4.2), and ultrasonic extraction is performed for 3h; after the extraction, the extract and the residue are filtered out; the above extract is used to remove the solvent using a rotary evaporator and concentrated to 3.0000g. The above concentrated extract is placed in a 20mL crucible, covered with a crucible lid, and placed in a 550℃ muffle furnace for heat treatment for 2h. The crucible is then placed in a dryer and cooled to room temperature, and the mass of the residue is weighed to be 0.0300g (M1). F=M1 / M c ×100%, calculated F=0.30%.

[0080] It has been verified that the petroleum coke is high-quality raw coke.

[0081] The graphite is prepared by using the petroleum coke, specifically:

[0082] The petroleum coke was successively shaped and graphitized at 3090°C for 2h to obtain a graphite product.

[0083] Example 2

[0084] This embodiment is basically the same as embodiment 1, except that the preparation method of graphite is different, specifically:

[0085] The petroleum coke is shaped and graphitized at 2900°C for 2 hours to obtain a graphite product.

[0086] Example 3

[0087] This embodiment is basically the same as embodiment 1, except that the preparation method of graphite is different, specifically:

[0088] The petroleum coke was shaped and graphitized at 3090°C for 2 hours to obtain a graphitized product. 5% asphalt was added to the graphitized product, stirred and mixed thoroughly, and then carbonized at 1150°C for 8 hours.

[0089] Embodiment 4-5

[0090] Examples 4-5 only provide a method for verifying whether the petroleum coke is high-quality green coke.

[0091] Embodiment 4-5 is basically the same as embodiment 1, except that:

[0092] Group Example 1 Example 4 Example 5 Solvents Tetrahydrofuran Chloroform Ethyl acetate Solvent polarity 4.2 4 4.5 F-number 0.30% 0.29% 0.31%

[0093] It can be seen from the above table that the F values ​​obtained in Examples 4 and 5 are still approximately 0.30%. This shows that although the solvents are different, the calculated F values ​​are still the same, indicating that different solvents within the polarity range defined in the present invention can be used to extract green coke to obtain F values.

[0094] Embodiment 6, 7

[0095] Examples 6 and 7 are substantially the same as Example 1, except that the heat treatment temperature in the method for verifying whether the petroleum coke is high-quality green coke is different.

[0096] Group Example 1 Example 6 Example 7 Heat treatment temperature 550℃ 500℃ 600℃ F-number 0.30% 0.30% 0.30%

[0097] It can be seen from the above table that the F values ​​obtained in Examples 6 and 7 are still 0.30%. This shows that although the heat treatment temperatures are different, the calculated F values ​​are still the same, indicating that heat treatment within the heat treatment temperature range specified in the present invention can be used to calculate the F value.

[0098] Examples 8-10

[0099] Examples 8-10 are basically the same as Example 1, except that the types of coke are different.

[0100] As shown in Table 1.

[0101] Group Example 1 Example 8 Example 9 Example 10 F-number 0.30% 0.10% 0.56% 0.43%

[0102] The coke F values ​​provided in the above embodiments are all greater than 0.10%.

[0103] Comparative Examples 1-3

[0104] Comparative Examples 1-3 are substantially the same as Example 1, except that the types of coke are different, as shown in Table 1.

[0105] Group Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 F-number 0.30% 0.02% 0.06% 0.003%

[0106] The coke F values ​​provided in the above comparative examples are all less than 0.10%.

[0107] Experimental example

[0108] The graphites obtained in Examples 1-3, 8-10 and Comparative Examples 1-3 were made into negative electrode sheets, which were then assembled into batteries to verify their electrochemical properties.

[0109] The specific method of making graphite into batteries is: graphite is evenly mixed with SBR, CMC, and SP in a ratio of 95.5:2:1.5:1, coated on copper foil, dried and rolled to form pole pieces, and assembled with metal lithium sheets into button batteries.

[0110] The specific method of electrochemical performance test is: 0.1C constant current charge and discharge, charge and discharge voltage of 0.05~2.0V, test the capacity and first coulomb efficiency of button cell; rate performance is the ratio of capacity under 3C and 0.5C current. The test results are shown in Table 1.

[0111] Table 1 Graphite parameters and electrochemical performance test results obtained in each embodiment and comparative example

[0112] Group Graphitization degree Capacity (mAh / g) First effect (%) Rate performance (%) Example 1 91.8 342.5 96.1 78.5 Example 2 91.0 340 95.1 78.0 Example 3 92.5 344.7 94.0 83.7 Example 8 93.8 352.8 97.0 79.1 Example 9 93.4 349.3 95.7 73.0 Example 10 92.3 344.0 92.1 75.5 Comparative Example 1 92.8 345.6 94.9 57.9 Comparative Example 2 93.5 351.0 95.6 62.5 Comparative Example 3 91.8 338.0 96.0 54.1

[0113] The rate performance of multiple embodiments provided by the present invention is maintained above 70%, while the rate performance of the comparative example is relatively poor, indicating that the graphite prepared in the embodiments of the present invention can be used as the negative electrode material of high-rate fast-charging lithium batteries.

[0114] Comparing the comparative examples with Examples 1 and 8-10, the graphite obtained in the comparative examples has poor rate performance after being made into batteries, which shows that the performance of graphite prepared by using raw coke with an F value of less than 0.10% as raw material will be significantly worse than that of graphite prepared from raw coke with F ≥ 0.10%. This shows that the raw coke with F ≥ 0.10% provided by the present invention is high-quality raw coke for preparing high-rate fast-charging graphite negative electrode.

[0115] In summary, the green coke provided by the present invention has F≥0.10%, so the green coke can be used to prepare graphite to obtain a graphite product with good electrochemical properties.

[0116] The graphite provided by the present invention has better electrochemical properties because the raw coke provided by the present invention is selected as the raw material, and can be used as the negative electrode material of a high-rate fast-charging lithium battery.

[0117] The method for judging high-quality raw coke for making graphite provided by the present invention can be used to judge whether the raw coke can produce graphite with good performance, and in particular can be used to judge whether the raw coke can produce graphite suitable for preparing the negative electrode of high-rate fast-charging lithium battery.

[0118] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A raw coke, characterized in that: The particle size of the green coke is 1 to 100 μm, and F is ≥ 0.10%; Where F = M1 / M c ×100%, where M c is the mass of the raw coke, M1 is the mass of the residue obtained by heat treating the substance dissolved in the solvent after the raw coke is extracted with a solvent, the solvent polarity parameter of the solvent is 4.0-4.5, and the heat treatment condition is 500-600°C in an air atmosphere.

2. The raw coke according to claim 1, characterized in that The solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran; Preferably, the particle size of the green coke is 6 to 15 μm; Preferably, the green coke is petroleum coke, needle coke or pitch coke.

3. The raw coke according to claim 1 or 2, characterized in that: The mass of the residue is determined by: The green coke is extracted with the solvent, and the extract is subjected to heat treatment, or the extract is concentrated to obtain a concentrated solution and then subjected to heat treatment to obtain a residue, the mass of which is M1; Preferably, the concentration is to a coke quality M c 1 / 4 to 1 / 2 of the total weight of the concentrate is obtained; Preferably, the heat treatment time is 2 to 3 hours.

4. A graphite, characterized in that: The method is prepared by graphitizing the raw coke as claimed in any one of claims 1 to 3.

5. The graphite according to claim 4, characterized in that The 3C / 0.5C capacity retention rate of the graphite is greater than 70%; Preferably, the graphitization degree of the graphite is greater than 90%.

6. A method for preparing graphite, characterized in that: include: The green coke according to any one of claims 1 to 3 is graphitized.

7. The preparation method according to claim 6, characterized in that: The temperature of the graphitization treatment is 2800-3200°C: Preferably, the process further comprises shaping the green coke before graphitization; Preferably, a graphitized product is obtained after graphitization, and the graphitization includes: coating asphalt or tar on the surface of the graphitized product particles, carbonizing at 1100-1300° C. for 7-8 hours, and the mass ratio of the asphalt or tar to the graphitized product is 0.01-0.05:

1.

8. A negative electrode, characterized in that It is made from the graphite as claimed in claim 4 or 5.

9. A fast-charge lithium-ion battery, characterized in that: Comprising the negative electrode as claimed in claim 8.

10. A method for determining the coke production in graphite production, characterized in that: include: The mass is M c The raw coke is extracted with a solvent, and the obtained substance dissolved in the solvent is heat-treated to obtain a mass M1 of the residue obtained by the heat treatment, wherein the solvent polarity parameter of the solvent is 4.0 to 4.5, and the heat treatment condition is 500 to 600° C. and air atmosphere; According to the formula F = M1 / M c ×100% to calculate the F value. If F≥0.10%, it is high-quality green coke for graphite production. Preferably, the solvent is selected from at least one of chloroform, ethyl acetate and tetrahydrofuran; Preferably, the particle size of the green coke is 1 to 100 μm; preferably, the particle size of the green coke is 6 to 15 μm; Preferably, the method for obtaining the mass M1 of the residue is: The green coke is extracted with the solvent, and the extract is subjected to heat treatment, or the concentrated solution is concentrated and then subjected to heat treatment to obtain a residue, and the mass of the residue is M1; Preferably, the coke is concentrated to a mass M of c 1 / 4 to 1 / 2 of the total weight of the concentrate is obtained; Preferably, the heat treatment time is 2 to 3 hours.